Pengaruh Unsur-unsur Motivasi terhadap Produktivitas Tenaga Kerja Perusahaan - Noegroho, Tjitra Oentoeng (Jurnal Widya Manajemen & Akuntansi, 2002)
Inefficient and ineffective working, high cost a company bears, decreasing of Indonesian economic development are three cases that connect to each other and have a direct influence on the productivity of the company. It means when the Indonesian economic development goes down, it causes higher and higher expenses the company should pay the continue production or just to survive. In that case something must be done to make the company work more efficiently and effectively. One way is by increasing the employees' productivity. However, to increase employees' productivity needs support from both sides, not only the employees' side but also that of the company. Employees' productivity can be increased by gaining the right motivation, whether material or immaterial motivation. A combination of both motivation can be done to give the best result of gaining the right motivation. Position of the employee must also be considered in gaining the right motivation because different position and physical working environment need different treatment of motivation.